Lineage-specific targets of positive selection in three leaf beetles correspond with defence capacity against their shared parasitoid wasp - Yang, Xuyue; Tunström, Kalle; Slotte, Tanja; Wheat, Christopher W.; Hambäck, Peter A. (Heredity, 2025)
Parasitoid wasps are major causes of mortality of many species, making host immune defences a common target of adaptive evolution, though such targets outside model species are poorly understood. In this study, we used two tests of positive selection to compare across three closely related Galerucella leaf beetles that show substantial differences in their phenotypic response to the shared parasitoid wasp Asecodes parviclava, their main natural enemy. Using a codon-based test, which detects excess amino acid fixations per locus along each species’ lineage, we found more evidence of positive selection on parasitoid-relevant immune genes in the species with the strongest immunocompetence (G. pusilla) compared with the species having weaker immunocompetence (G. tenella and G. calmariensis). Moreover, genes coding for the early phases in the immune response cascade were predominantly among the positively selected immune genes, providing targets for future functional genomic study to pin-point connections between genotypic and phenotypic differences in defences towards a parasitoid wasp. In contrast, genome-wide analyses of the haplotype frequency spectrum, which quantify selection over recent evolutionary time scales, revealed similar signatures of positive selection on immune genes across species. These results advance the field of host-parasitoid dynamics by providing novel insights into the tempo and mode of insect host evolutionary dynamics, and offering a framework for making genotype to phenotype connections for immunocompetence phenotypes.